Phylogenetic relationships among Southeast Asian climbing bamboos (Poaceae Bambusoideae) and the Bambusa complex - Goh, W.L.; Chandran, S.; Lin, R-S; Xia, N-H; Wong, K.M. (Elsevier, 2010)
A phylogenetic analysis of Bambusa and allies based on the plastid DNA non-coding regions rps16-trnQ trnC-rpoB trnH psbA and trnD-T and a partial nuclear GBSSI gene was carried out This included representatives from all four Bambusa subgenera (Including type species) a group of segregate Southeast Asian genera distinctive by their climbing-scrambling culms (Dinochloa Holttumochloa Kinabaluchloa Maclurochloa Soejatmia Sphaerobambos) and two other Bambusinae genera (Dendrocalamus Gigantochloa) The results do not support the present subgeneric classification of Bambusa The climbing Southeast Asian genera all of which include species previously placed in Bambusa are distinct from the ``core Bambusa group (type species and alliance) and the Bambusa complex generally (C) 2010 Elsevier Ltd All rights reserved